Pemanfaatan Jaringan Komputer Pada Laboratorium SMK Dr. Sjahrir Medan - Chandra, Tintin (STMIK TIME, 2014)
The beginner of Data communications done with direct contact. Since existence of computer network, hence all connection pass network. For that need optimal enableness so that infrastructure and medium of network do not without effect. One of the applying of computer network at laboratory of SMK Dr. Sjahrir. In computer network do not only having the character of Local Area of Network but can be used as by laboratory of internet. Computer laboratory used by Iesson time take place for subject requiring practical while laboratory of internet used by rest space. Existence of computer network hence student very assisted in transfer and spreading of information of server to client and do not require additional other depository medai in transfer of data.